Comparison of ultrasound and histopatological findings breast cancer between women aged below and above 40 years - Mohamad Saini, Suraini; Bahari, Norafida; Ibrahim, Idris; Abu Hassan, Hasyma; Abdul Rahim, Ezamin; Ibraheem, Shahad Abdul Wahhab; Baharom, Nuratika; Lim, Shi Ni (Auricle Technologies, 2021)
Breast cancer is the most common cancer among females, but breast cancer incidence in young women is low. There are limited studies of breast cancer in this age group in Malaysia, while there are conflicting data regarding these women's prognosis compared to older patients. This study describes the common features presented by breast carcinoma on histopathological and ultrasound findings. Objective: To comparethe ultrasound findings and histopathological characteristics of breast cancer for women aged below 40 years and those aged 40 years and above. Methodology: This was a retrospective, cross-sectional study using secondary data, in which the data was collected respectively from patient's clinical histories, radiology findings, and histopathology reports of patients with breast cancer in Hospital Serdang from 1 January 2009 until 31 December 2018. Patients were divided into two age groups (ages below 40, ages 40 and above). Results: 205 patients were included in this study. The most common type of breast carcinoma is invasive ductal carcinoma. Common features are grade IIbreast cancer cells,DCIS high grade, stage 2(TNM), tumour size ofT2andlymph node invasion. The majority of tumours are positive with oestrogen receptor, progesterone receptor, and HER2 receptor. Conclusion: Younger age group has a similar feature with the older age group, except they have late stage and progesterone negativity. There is no significant association between age group, ultrasound, histological features, and breast carcinoma receptors.